María Josefa Trinidad Enríquez Ladrón de Guevara (1846-1891): The intellectual construction of the first female Peruvian lawyer - Flores Heredia, Gladys (2022)
This article focuses on the figure of the first Peruvian female lawyer: María Josefa Trinidad Enríquez Ladrón de Guevara. Therefore, it will present and explain some of the significant moments of her life experience that served to build her image as a Peruvian intellectual in the field of law.